Analisis Harga Pokok Produksi Menggunakan Metode Full Costing dan Variabel Costing pada UD Surya Tani di Luwu Utara - Muhammad Zadli Syahdi (STIE AMKOP, 2021)
This study aims to determine which method of calculating the cost of production is the most appropriate to be applied in the company. This study uses a case study method that focuses on the analysis of cost calculations in determining the cost of production for 1 kg of rice. This research was conducted using two approaches to determining the cost of production, namely 1.) The full costing method is a method that treats all production costs as product costs regardless of whether the costs are variable or fixed. 2.) the variable costing method, namely the method of determining the cost of production that only includes or charges variable production costs as an element of the cost of production, while fixed production costs are considered as period costs which are directly charged to the income statement. The results of the analysis show that the evaluation of the calculation of the cost of production in the company is not the same as the cost of production which is calculated using the full costing and variable costing methods. Where the cost of production according to the company's estimate is Rp.7,667-, per kg, while the cost of production according to the full costing method is Rp.8,410-, per kg and the cost of production using the variable costing method is Rp.8,294-, per kg. The difference in the cost of production estimated by the company with the other two methods occurs because the cost calculations carried out by the company are not accurate because they do not calculate factory overhead costs as a whole such as depreciation of buildings and other equipment.